PRENATAL CONTROL AND MATERNAL PERINATAL OUTCOME - Tipiani, Oswaldo (2015)
OBJECTIVE: To determine prenatal care influence on maternal and infant mortality and morbidity. DESIGN: Prospective cohort study. SETTING: Arzobixpo Loayza National hospital, Lima, Peru, a teaching hospital. PATIENTS: Four hundred and fifty-five pregnant women hospitalized until delivery between August 1st and October 30th, 2005. INTERVENTIONS: Patients were divided in 4 groups according to the number of prenatal care visits: no prenatal visits (n= 30), 1 to 4 visits (n= 85), 5 to 8 (n= 216) and 9 or more (n= 124). Kessner’s index was used to determine the quality of prenatal care. MAIN OUTCOME MEASURES: Maternal and perinatal morbidity and mortality. RESULTS: According to Kessner’s index 115 pregnant women (25,3%) had inadequate prenatal care and 340 (74,7%) intermediate or adequate prenatal care. Those with inadequate prenatal care presented 6 times higher risk of having a premature child (RR 6,1; IC 2,7-13,7) and 4 times higher risk for a low birth weight newborn (RR 4,3; IC 2,2-8,4). The lower number of prenatal care visits correlated with a lower birthweight and a higher incidence of preterm delivery (Anova, p< 0,05). Regression showed that the most important risk of inadequate prenatal care was preterm delivery (OR 1,16; IC 1,09-1,22) and low birthweight was associated (OR 1,8; IC 95% 1,63- 1,99). A lower number of prenatal visits was also associated with less education (Anova, p<0,01). We found no statistically significant difference in the incidence of anemia, cesarean sections, third trimester hemorrhage, gestational hypertensive disorders, post partum hemorrhage, premature rupture of membranes, and post partum morbidity. CONCLUSIONS: In our population, a lower number of prenatal visits and inadequate prenatal care resulted in higher incidence of preterm deliveries and consequent lower birthweight. Notwithstanding, the number of visits could be reduced to five in uncomplicated pregnancies.